(untitled) (International journal of artificial intelligence, 2025)
This paper examines the significance of artificial intelligence (AI) within the educational sphere, focusing on the opportunities it creates for enhancing teaching and learning. It provides a concise overview of AI-driven applications that facilitate more effective educational processes. Moreover, the study addresses potential challenges and risks associated with the use of AI in education that require critical consideration.